Spatial accessibility to kindergartens using a spectrum combinational approach: Case study of Shanghai using cellphone data. (July 2021) - Chen, Zifeng; Zhou, Xingang; Yeh, Anthony GO
Spatial accessibility to kindergartens is a critical issue related to the transport safety of children. Young children should be escorted to kindergartens by adults, and trips to kindergartens are occasionally dependent on parents' home–work trips because parents may escort their children to kindergartens en route to work. Many types of school trip can be categorized into two main types: "Home–School" and "Home–School–Work" trips. However, existing studies have tended to focus on only one type of school trip and have disregarded the other type in the assessment of accessibility. The present study examines accessibility to kindergartens by considering both types of school trips. The basic two-step floating catchment area method is used to measure the accessibility of "Home–School" trips and the commuter-based two-step floating catchment area is used for "Home–School–Work" trips. This study proposes a spectrum combinational approach, which combines both types of trips according to their actual percentages, to provide a realistic assessment of accessibility to kindergartens. An empirical study is conducted in Shanghai by combining cellphone big data and traditional data from a census. Results indicate that, compared with the spectrum combinational approach, the inequality of accessibility would be underestimated if we only focus on "Home–School" trips in the measurement of accessibility, but overestimated if we only focus on "Home–School–Work" trips. The proposed spectrum combinational approach, by modifying the trip assumptions on which accessibility evaluation is based, constitutes a novel and more realistic accessibility measurement of spatial accessibility to kindergartens.